184 Increasing Insulin Sensitivity in the Endothelium Leads to Reduced Nitric Oxide Bioavailability. (6th June 2015) - Viswambharan, Hema; Sukumar, Piruthivi; Sengupta, Anshuman; Cubbon, Richard; Imrie, Helen; Gage, Matthew; Haywood, Natalie; Yuldasheva, Nadira; Skromna, Anna; Gatenby, Kate; Galloway, Stacey; Santos, Celio; et al.
Abstract : Introduction: Insulin resistance is known to precede Type 2 diabetes (T2DM). Insulin mediated release of the endothelial cell (EC) derived anti-atherosclerotic molecule, nitric oxide (NO) is blunted in patients suffering from insulin resistance T2DM. We examined the effects of enhancing EC insulin sensitivity in vivo, by generating a novel transgenic mouse, over-expressing Type A human Insulin Receptor (HIRECO) restricted to EC. Methods: Western blotting and RT-PCR were carried out on tissues and isolated endothelial cells from lungs to measure protein levels and mRNA expression, respectively. NADPH-dependent lucigenin-enhanced chemiluminescence was used to measure superoxide anion levels. Isolated thoracic aortic rings suspended in an organ bath were used to determine vasomotor functions. eNOS activity was examined by citrulline assay with 14 C-labelled L-arginine. HIRECO were compared to wild type littermates. Results: Over-expressing human insulin receptors in EC had no significant effect on morphological features, metabolic phenotype or blood pressure of HIRECO. HIRECO demonstrated significant EC dysfunction measured by a blunted endothelium-dependent vasorelaxation to acetylcholine and reduced basal NO release. EC-independent response to sodium nitroprusside remained unchanged. EC dysfunction observed in the organ bath was normalised by a NADPH oxidase-specific inhibitor peptide, gp91ds-tat as well as the superoxide dismutase mimetic, MnTmPyp. HIRECO demonstrated significant increase in superoxide anion release compared to WT littermates. This data was supported by a concomitant increase in NADPH oxidase isoform, NOX2 protein expression. Basal eNOS and Akt phosphorylation levels in isolated EC of HIRECO mice were enhanced compared to WT mice. Interestingly, insulin-stimulated eNOS phosphorylation and activation was decreased, whereas Akt phosphorylation remained unchanged. eNOS tyrosine phosphorylation mediated by proline-rich tyrosine kinase (PYK2) was significantly enhanced in EC from HIRECO mice. In order to investigate, if the perturbations of insulin signalling in the EC have a pathological outcome, HIRECO mice were crossed with ApoE-knockout mice. These mice demonstrated a significant enhancement of plaque formation in aorta, as well as the aortic root. Conclusions/implications: These data show that increasing EC insulin sensitivity leads to reduced bioavailability of NO. These data demonstrate for the first time that increased insulin signalling in EC increases the generation of superoxide anion via activation of NOX2 NADPH oxidase and reduced NO production in response to insulin due at least in part to increased EC PYK2 activity leading to a pro-atherosclerotic state.